MAGMA GENESIS AND CRUSTAL CONTAMINATION OF CONTINENTAL INTRAPLATE LAVAS IN NORTHWESTERN SYRIA - Krienitz M.-S.; Haase K.M.; Mezger K.; Eckardt V.; Shaikh-Mashail M.A. (My University, 2006)
The Miocene to Quaternary lavas of northwestern Syria range from basanite, alkali basalts, and tholeiites to basaltic andesites, hawaiites, and mugearites. Crustal assimilation and fractional crystallization processes (AFC) modified the composition of the mantle derived magmas. Crustal assimilation is indicated by decreasing Nb/U (52.8-17.9) and increasing Pb/Nd (0.09-0.21) and by variable isotopic compositions of the lavas (87Sr/86Sr: 0.7036-0.7048, 143Nd/144Nd: 0.51294-0.51269, 206Pb/204Pb: 18.98-18.60) throughout the differentiation. Modeling of the AFC processes indicates that the magmas have assimilated up to 25% of continental upper crust. The stratigraphy of the lavas reveals decreasing degrees and increasing depths of melting with time and the strongly fractionated heavy rare earth elements indicate melt generation in the garnet stability field. Modeling of melt formation based on trace element contents suggests that 8-10% melting of the asthenospheric mantle source produced the tholeiites, whereas basanite and alkali basalts are formed by 2-4% melting of a similar source. © Springer-Verlag 2006.
Keywords: Кайнозой::Четвертичная; Кайнозой::Неоген::Миоцен; Cenozoic::Quaternary; Cenozoic::Neogene::Miocene